PROSES PENANAMAN KARAKTER GEMAR MEMBACA PADA SISWA KELAS III MELALUI PELAKSAAAN PROGRAM LITERASI DI SDN BANJAR SARI 5 - Irtia Dati Salsabilah; Zerri Rahman Hakim; M. Taufik (Universitas Trilogi, 2020)
This study was designed to describe the process of planting reading characters in grade III students through the literacy implementation program at SDN Banjar Sari 5. The research subjects were teachers and students. The object of this research is the character of reading fondly through the literacy program. This research uses descriptive qualitative. Data collection procedures in research are interviews, observation, and documentation. Data analysis uses analysis techniques namely data reduction, displaying data and drawing conclusions. Checking the validity of the data using triangulas, specifically methodological triangulation. The results of the study complement what is meant by fond of reading at school with habituation activities through the literacy program going pretty well, both in direct learning and online which is held by the school as the school which manages this.